A Survey Of School-Age Children's Maternal Knowledge and Attitudes About Obese in The Working Area of The Talang Banjar Health Center, Jambi City - Ramadani, Ria; Deswita, Deswita; Novrianda, Dwi (Universitas Malahayati, 2024)
ABSTRACT The global incidence of childhood obesity is one of the main public health issues. Indonesia is one of the nations where overweight and obesity rates are rising the fastest, and the country also suffers from severe triple burden malnutrition (TBM). Children who are obese may experience detrimental impacts to their physical and mental health. Parents' knowledge, attitudes, and behaviors—especially those of mothers—have a big influence on how effectively kids manage their weight. Purpose to ascertain the nature of mothers' attitudes and knowledge on obesity in school-age children in the Talang Banjar Health Center's working area in Jambi City. This kind of research was carried out in January 2024 in the Talang Banjar Health Center Working Area, Jambi City, using a cross-sectional design and quantitative analysis. The mothers with school-age children comprise the researcher's population. With the use of a straightforward random sampling technique, the study's sample size was 138. Questionnaires on knowledge and attitudes were the instruments utilized. use SPSS software for data analysis. Sixty-one percent of the respondents were in the late adult (36–45 year) age range. 75.4 percent of respondents have completed high school, MAN, or SMK, and 72.5 percent of respondents are housewives. These are the categories with the most education levels among respondents. The level of maternal knowledge about obesity in school-age children is good knowledge (25.4%), sufficient knowledge (33.3%), lack of knowledge (41.3%), and most of the maternal attitude categories have a negative attitude category (54.3%). The results of this study demonstrate that respondents' attitudes and understanding on childhood obesity are lacking. Keywords: Child Obesity, Maternal Knowledge, Maternal Attitude